Electromechanical actuator having ceramic insulator and method of manufacture thereof - Patents.com
By employing a ceramic insulator with a smaller grain size and multiple layers, the actuator's durability is enhanced in humid conditions, addressing moisture-induced degradation and crack formation, resulting in a prolonged service life and increased electromechanical expansion.
Patent Information
- Application Number
- JP2021563317
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-26
- Filing Date
- 2020-04-07
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2040-04-07
AI Technical Summary
Ceramic-coated electromechanical actuators face limitations in humid environments due to moisture-induced degradation, leading to reduced service life and mechanical failure from crack formation during piezoelectric expansion.
A ceramic insulator with a smaller average grain size than the ceramic base material is used, combined with multiple layers to prevent moisture penetration and enhance crack resistance, allowing for higher electromechanical expansion without compromising durability.
The solution extends the actuator's service life in humid conditions by preventing crack formation and maintaining electromechanical expansion, achieving a mean time to failure (MTTF) of at least 10,000 hours under 2 kV-DC/mm and 92% humidity.
Smart Images

Figure 0007603019000002 
Figure 0007603019000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromechanical actuator according to the preamble of claim 1, comprising a stack arrangement made of a ceramic base material and electrodes having electromechanical properties and a ceramic insulator for the use of the actuator in a wet environment. Such actuators are also called multilayer actuators or linear actuators. Further aspects of the invention relate to a method for producing an actuator with a ceramic insulator and a method for controlling such an actuator. [Background technology]
[0002] The service life of electromechanical actuators is limited, inter alia, by atmospheric moisture-mediated degradation mechanisms when used in static or quasi-static applications. In particular, the diffusion or penetration of water vapor molecules into the stack arrangement leads to a deterioration of the electrical and elastic behavior of the actuator, and thus to a partial or total loss of the actuator's function. An increased service life can be obtained, in particular by an insulation of the actuator, which comprises or is made of a ceramic material. Electromechanical or piezoelectric actuators with such ceramic insulation are known from DE 100 21 919 C2. In comparison with actuators with polymer insulation, ceramic-insulated actuators when controlled with direct current (DC) can have a service life (Mean Time To Failure (MTTF)) that is two to three orders of magnitude higher.
[0003] A piezoelectric actuator is also known from EP 2 530 756 A1, on whose sides is provided an inorganic layer, for example made of lead zirconate titanate (PZT). US 7,065,846 B2 also discloses a piezoelectric actuator with a ceramic insulator.
[0004] However, this type of ceramic insulator has physical limitations. Ceramic-coated actuators have so far typically shown an electrically induced piezoelectric expansion of about 1.0‰-1.1‰ of the actuator's active length when controlled with a field strength of 2 kV-DC / mm. If the electrically induced piezoelectric expansion were to be increased, for example, to >1.25‰ of the active length, for example by optimizing the electromechanical material system lead zirconate titanate (PZT), it would result in uncontrolled crack formation and growth in the ceramic insulator, which would have a negative effect on the actuator's useful life. Due to the design of the linear actuator, the electrodes do not extend into the insulator so that they are precisely protected from moisture. As a result, the ceramic insulator can only be excited by electrical stray fields, which inevitably results in a reduced or even absent piezoelectrically induced expansion of the ceramic insulator. For this reason, mechanical tensile stresses arise during the actuation or expansion of the actuator, which, due to continuous or alternating loading, can lead to the formation of cracks, causing the actuator to fail or lose its function, or reducing its useful life in wet environments.
[0005] WO 2017 / 032868 A1 discloses a piezoelectric multilayer actuator having a protective layer fabricated on the actuator surface by airflow deposition (see page 4, lines 14-16), and a protective layer made of split ceramic particles and connected to each other, for example by annealing (see page 4, lines 28 to page 5, line 2).
[0006] Since this protective layer is very dense, porosity-free and does not contain "grain boundaries" as formed by sintering processes, it is assumed that the protective layer will remain crack-free during operation even if the actuator has a small thickness (see page 5, lines 5-10). EP 2 667 425 B1 discloses a piezoelectric element with an inorganic coating in which metal particles are dispersed. There is a risk that the metal particles will cause conductive paths to form in the coating, especially at defects, which may accelerate failure mechanisms. The invention is based on the object of providing an electromechanical actuator with an extended service life, in that the formation of cracks in the sintered ceramic insulator is prevented, and which is also accompanied by an increased electromechanical expansion. Summary of the Invention [Means for solving the problem]
[0007] The object of the invention is met by an electromechanical actuator according to claim 1, by a method for manufacturing an electromechanical actuator according to claim 10, and by a method for controlling an electromechanical actuator according to claim 14. Advantageous developments of the invention are claimed in the dependent claims.
[0008] The electromechanical actuator according to the invention comprises a stack arrangement made of ceramic-based materials and electrodes having electromechanical properties, and a ceramic insulator for use in the actuator in a wet environment, the structure of the ceramic insulator having a smaller average grain size than the structure of the ceramic-based material. The specific selection of the ceramic insulator, whose structure has a smaller average grain size than the structure of the ceramic-based material, increases the strength of the ceramic insulator (yield strength, see Hall-Petch relationship) and its resistance to crack formation. By increasing this resistance, an extended service life of the actuator can be obtained even in the case of higher electromechanical expansion, which can be achieved by a larger average grain size in the structure of the ceramic-based material. This is because the electrically induced expansion suitable for use of the material increases with increasing grain size. The ceramic-based material is preferably a piezoelectric-based material. The electromechanical properties of the actuator are preferably modified or set, for example by polarization after shaping of the ceramic-based material.
[0009] It may be advantageous for the ratio of the average grain size of the insulator to the ceramic base material to be 3 / 4 or less, preferably 1 / 2 or less, particularly preferably 1 / 3 or less. The smaller the average grain size of the insulator, the greater the strength and resistance of the insulator to crack growth. The stated ratio achieves advantageous results, taking into account the mechanical interaction between the base material and the insulator.
[0010] Furthermore, it may be advantageous for the insulator to have a mean grain size of less than 20 μm, preferably less than 5 μm, particularly preferably less than 1 μm.
[0011] In addition, it has been found that it may be practical for the average grain size of the ceramic base material to preferably continuously decrease towards and preferably beyond the insulator, whereby expansion or tensile cracking in the region where the insulator abuts the ceramic base material may be avoided.
[0012] It has been found that it can be advantageous for the insulator to be made of an electromechanical material, preferably a piezoelectric material, particularly preferably a piezoelectric ceramic material.
[0013] In addition, it may be advantageous for the insulator to be impermeable to water vapor / moisture, which prevents water vapor molecules from diffusing or penetrating into the stack arrangement.
[0014] It may be advantageous for the insulator to be made of at least one layer, preferably two or three layers, with a total thickness of the insulator of not more than 500 μm, preferably not more than 100 μm, particularly preferably not more than 60 μm. By providing several layers, manufacturing defects such as holes or pores in individual layers can be covered by other layers, which results in an improvement of the insulation. The possibility of end-to-end defects throughout the thickness of the insulator is then reduced with each additional layer.
[0015] Additionally, it may be advantageous for the insulator to comprise a material composition that is substantially the same as or different from the ceramic base material.
[0016] In addition, it may be beneficial for two external electrodes to be provided for contacting the electrodes in the stacked arrangement, either on the same outer surface of the actuator or on two different outer surfaces, with at least one electrode-free outer surface of the actuator comprising a ceramic insulator. The actuator can be reliably insulated by attaching the external electrodes and providing a ceramic insulator on the electrode-free outer surface.
[0017] It may be advantageous for the ceramic base material and the electrodes to be arranged along a stack axis, the stack arrangement having two end faces aligned perpendicular to the stack axis and at least one side face extending between the end faces, and for a ceramic insulator on at least one side face to extend from one end face to the other end face. Providing a ceramic insulator on these sides prevents diffusion or penetration of water vapour molecules between the electrodes and the ceramic base material.
[0018] Another aspect of the invention relates to a method for manufacturing an electromechanical actuator, in particular an actuator according to one of the preceding configurations, comprising the steps of: A: forming a stack arrangement from electrodes and from a ceramic base material having electromechanical properties; B: providing a ceramic insulator in a stack arrangement such that the structures of the insulator have an average grain size smaller than the structures of the ceramic base material.
[0019] Furthermore, it may be advantageous for the method to comprise at least one of the following substeps: A1: Partial step of forming a stack arrangement from electrodes and from green tapes made of ceramic base material; A2: A partial step of sintering the stack arrangement so that the ceramic base material is converted into a solid ceramic structure.
[0020] However, it may also be beneficial for the method to comprise at least one of the following substeps: B1: A partial step of applying at least one, some or all layers of an insulator onto the stack arrangement by coating, injection moulding, plasma spraying, preferably with a green tape, by dip coating, spraying, preferably in a ceramic slurry, and / or by a sol-gel process; B2: A partial step of sintering the ceramic insulator and, optionally, the ceramic base material, so that the ceramic insulator and, optionally, the ceramic base material are converted into a solid ceramic structure; B3: A partial step of setting the average grain size of the insulator and possibly of the ceramic base material by selecting different materials for the ceramic base material and the ceramic insulator and / or by selecting the processing parameters during sintering.
[0021] It may also be beneficial for the method to comprise the steps of: C: Poling the ceramic base material, and preferably the ceramic insulator, to set the electromechanical properties of the actuator.
[0022] It may also be advantageous that while the stack arrangement in step A is formed from the electrodes and the ceramic base material along a stack axis, with the stack arrangement comprising two end faces oriented perpendicular to the stack axis and at least one side face extending between the end faces, the stack arrangement in step B is provided with a ceramic insulator, the latter extending from one end face to the other on at least one side face. As already mentioned above, providing a ceramic insulator on these sides prevents the diffusion or penetration of water vapour molecules between the electrodes and the ceramic base material.
[0023] Another aspect of the invention relates to a method for controlling an electromechanical actuator, in particular an actuator according to one of the preceding configurations, in which a quasi-static expansion of the effective length of the actuator of 1.25‰ or more and a mean time to failure (MTTF) of the actuator of 10,000 hours or more are achieved at a field strength of at least 2 kV-DC / mm at room temperature and a humidity of preferably at least 80%, preferably at least 85%, preferably at least 90%, particularly preferably at least 92%.
[0024] An additional aspect of the invention relates to a method for controlling an electromechanical actuator, in particular an actuator according to one of the preceding configurations, in which a quasi-static expansion of the effective length of the actuator of 1.25‰ or more and a mean time to failure (MTTF) of the actuator of 500 hours or more are achieved at a field strength of at least 2 kV-DC / mm at 90° C. and a humidity of preferably at least 80%, preferably at least 85%, preferably at least 90%, particularly preferably at least 92%.
[0025] Terms and Definitions Green tape made from ceramic materials The flexible tape produced from the ceramic slurry by a tape casting process is called a green tape made of ceramic material.
[0026] Insulation The insulator is a protective layer that prevents moisture from penetrating into the stack actuator.
[0027] Actuator The term actuator is used synonymously for stack actuator, multi-layer actuator, or linear actuator.
[0028] Ceramic-based materials with electromechanical properties A ceramic base material with electromechanical properties is a material that undergoes mechanical (elastic) deformation when a voltage is applied. The starting point of this material can be a ceramic powder that is sintered for shaping. The microstructure of the sintered ceramic is a polycrystalline material, whose crystallites have magnetic domains with dipoles, the orientation of which is statistically distributed throughout the material. To set the electromechanical properties of the actuator, the dipoles are preferably commutated by polarization.
[0029] polarization For the fabrication of most electromechanical actuators, the material is poled after sintering by applying an external unidirectional field, which results in a global commutation of the dipoles, thus allowing the desired electromechanical properties of the actuator to be set. [Brief description of the drawings]
[0030] [Figure 1] 2A-2C show a top view and cross-sections along lines AA and BB of an actuator according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS 1 shows an electromechanical actuator consisting of a rod-shaped stack arrangement 1 made of a ceramic base material having electromechanical properties and electrodes 2 arranged alternately on both sides of the actuator. Each of these two sides is provided with an external electrode 3 for contacting the electrodes 2. The external electrodes 3 are each connected to a connection lead 4. The sides of the actuator not covered by the external electrodes are provided with a ceramic insulator 5.
[0032] The basic structure of this stack arrangement is known from DE 100 21 919 C2 and will not be described in detail here, instead the inventive differences from the known stack arrangement will be described and mainly discussed below.
[0033] In accordance with the present invention, the structure of the ceramic insulator 5 has a smaller average grain size than the structure of the ceramic base material. The smaller average grain size results in smaller pore sizes or porosity in the structure of the ceramic insulator 5, which in turn reduces the size of defects in the structure and inhibits the formation or growth of cracks.
[0034] The ceramic base material and the electrodes are preferably arranged along the stack axis. The stack arrangement consisting of the ceramic base material and the electrodes has two end faces aligned perpendicular to the stack axis and at least one side face extending between the end faces, and the ceramic insulator on at least one side face extends from one end face to the other end face. Without the ceramic insulator, the electrodes would be exposed on the peripheral side faces. Providing the ceramic insulator on these sides prevents diffusion or penetration of water vapor molecules between the electrodes and the ceramic base material.
[0035] In a preferred embodiment, the ratio of the average grain size of the insulator to the ceramic base material is ≦3 / 4, preferably ≦1 / 2, particularly preferably ≦1 / 3. The average grain size of the insulator can be ≦20 μm, preferably ≦5 μm, particularly preferably ≦1 μm.
[0036] The ceramic base material is preferably a piezoelectric ceramic material, such as lead zirconate titanate (PZT), but may alternatively be an electrostrictive or magnetostrictive material. The ceramic insulator 5 is likewise made of PZT or an oxide ceramic material and preferably also has piezoelectric properties.
[0037] The ceramic insulator 5 may consist of a single layer. In a preferred embodiment, however, the ceramic insulator 5 has several, in particular two or three, layers in order to cover defects caused by the manufacturing technique in one single layer with another. This may prevent the growth of cracks at the boundary between the two insulator layers. As a result, the ceramic insulator 5 may be made to be reliably impermeable to the penetration or diffusion of water vapor molecules into the stack arrangement. The individual layers may differ from each other in their composition or in their average grain size. The thickness of the individual layers is a multiple of the average grain size in this layer, preferably 5 to 20 times. In general, a small overall thickness of the ceramic insulator is aimed for, since the expansion of the ceramic base material is hardly limited by a thin insulator. In a preferred embodiment, the overall thickness of the insulator is equal to or less than 500 μm, preferably equal to or less than 100 μm, particularly preferably equal to or less than 60 μm.
[0038] A method according to the invention for the manufacture of an actuator, in particular an actuator according to the above embodiments, is described below.
[0039] The production of stack arrangements from ceramic base materials and electrodes having electromechanical properties is known in principle from DE 100 21 919 C2 but will be briefly outlined once again in order to improve understanding of the method according to the invention.
[0040] The starting point for the fabrication of the stack arrangement 1 is a ceramic powder material, preferably a PZT powder material, provided with a binder solution and a solvent. In a further step of the method, a ceramic slurry made of the powder material and the binder solution is poured to form a so-called green tape made of a ceramic base material, and the solvent evaporates. The flexible green tape is then cut to size and stacked. An electrode 2 is inserted between every two layers of a given number of green tapes. For this purpose, a metal paste is printed onto each green tape using a screen printing method. The stack arrangement 1 thus fabricated is then pressed isostatically.
[0041] The method according to the invention now provides such a stack arrangement 1, in which the ceramic insulator 5 is provided such that the structure of the ceramic insulator 5 has a smaller average grain size than the structure of the ceramic base material. For this purpose, at least one side of the stack arrangement 1 is applied with one or more green tapes, which in a preferred embodiment have a different material composition or have different material properties than the green tapes of the ceramic base material. The stack arrangement 1 and the ceramic insulator 5 are then jointly sintered, so that the green tapes of the ceramic base material and the ceramic insulator 5 are converted into a solid ceramic structure. By selectively setting the composition and / or properties of the starting materials of the ceramic base material and the ceramic insulator 5, a smaller average grain size can be obtained in the solid structure of the ceramic insulator 5 than in the structure of the ceramic base material. After sintering, the side of the actuator is applied with an external electrode 3, which establishes an electrical contact with the electrode 2 in the stack arrangement 1 and does not have the ceramic insulator 5. After the external electrode is applied, a unidirectional electric field is applied in order to generate a polarity for polarizing the ceramic base material and preferably the ceramic insulator 5.
[0042] The method described above is a one-stage process since the stack arrangement 1 and the ceramic insulator 5 are sintered together. In addition, it is also possible to carry out a two-stage process, in which the stack arrangement 1 is first sintered, then one or more layers of ceramic insulator 5 are applied onto the sintered stack arrangement 1 and the stack arrangement provided with the ceramic insulator 5 is sintered again. Different average grain sizes in the structure of the ceramic insulator 5 and the ceramic base material can be set, in particular by selective selection of the process parameters in the individual sintering stages, while the composition or properties of the starting materials of the ceramic base material and the ceramic insulator 5 may be substantially the same.
[0043] According to the above embodiment, the average grain size of the respective microstructure in the one-stage process is set substantially by the different compositions or properties of the ceramic base material and the starting material of the ceramic insulator 5, whereas in the two-stage process it is set substantially by the selection of the processing parameters in the individual sintering steps. However, the method according to the invention is not limited to such a one-stage or multi-stage method.
[0044] In addition, the desired average grain size in each microstructure may be set in a one-step process by suitable selection of processing parameters. Microwave sintering, which will be described in more detail below, leads to non-uniform heat distribution in the stack arrangement, and the energy emitted through the surfaces of the stack arrangement creates lower temperatures in the edge regions of the insulator, resulting in larger grain growth in the center than in the insulator.
[0045] A non-uniform temperature distribution in the stack arrangement during the sintering process is also possible by applying a suitable voltage to the actuator, since the resulting current flow generates heat and due to energy radiation at the surface of the stack arrangement, it has a lower temperature than its core region. The electric field in the interior of the stack arrangement resulting from the voltage can further favorably affect the grain growth or grain size distribution in the stack and insulator.
[0046] In addition, grain growth can be influenced by an external electric field in the sense described above (the gradual evolution of grain size in ceramic insulators) without there being a conductive contact with the actuator.
[0047] Furthermore, in the two-step process, different material compositions or properties may be used as well as different processing parameters in the individual sintering processes.
[0048] Some examples of the realization of different compositions or properties of the starting materials that may contribute to setting different average grain sizes in the respective structures are described below.
[0049] Firstly, it is reasonable to use a starting material for the ceramic base material, whose average grain size with typical sintering is large enough to achieve an expansion >1.1‰. For the ceramic insulator 5, this material may be doped with a grain growth inhibitor to suppress grain growth in the structure of the ceramic insulator 5 compared to the grain growth in the structure of the ceramic base material during the subsequent sintering process.
[0050] The starting material can then be used for the ceramic insulator 5, the average grain size of which is small enough to meet the strength requirements for the insulator with typical sintering. For the ceramic base material, this material may be doped with a grain growth accelerator to accelerate the grain growth in the structure of the ceramic base material compared to the grain growth in the structure of the ceramic insulator 5 during the subsequent sintering process.
[0051] Furthermore, the initial grain size of the ceramic base material and the starting material of the ceramic insulator 5 may be different. This means that a particularly finely ground powder can be used for the ceramic insulator 5 compared to the ceramic base material, which leads to a smaller average grain size in the structure of the ceramic insulator 5 even after sintering.
[0052] In addition, particularly in the case of PZT materials, one may choose a ceramic base material and starting material for ceramic insulator 5 that have different lead compatibility. If a starting material is chosen for the ceramic base material that has a higher lead compatibility than the starting material for ceramic insulator 5, the ceramic base material will remove some of the lead content from the ceramic insulator. This removal slows down the grain growth kinetics in ceramic insulator 5.
[0053] The above mentioned options for achieving different material compositions or material properties may be used alone or in combination to set the desired difference in average grain size in the respective microstructures.
[0054] The temperature or temperature profile over time, the holding time, the electric field in the environment, as well as the external atmosphere, in particular the oxygen content and the atmospheric pressure, essentially represent processing parameters that can be set for the respective sintering process and can contribute, alone or in combination, to achieving different average grain sizes in the respective microstructures.
[0055] In addition, the difference in the average grain size in the respective structures can also be obtained by using microwave sintering. Due to the dipole structure of the piezoelectric ceramic, heat develops in the volume of the component during microwave sintering. The heat is dissipated from the surface of the component to the cooler environment, i.e. the air and the walls of the sintering assembly, so that the sintering temperature of the surface, and therefore of the ceramic insulator 5, is lower than the core temperature of the ceramic base material. As a result of this temperature difference, the grain growth in the ceramic insulator 5 proceeds slower.
[0056] The method is not limited to the application of a layer of ceramic insulator 5 in the form of a green tape. There is also the possibility of applying the starting material of ceramic insulator 5 by injection molding, plasma spraying, dip coating in a ceramic slurry, spraying or by a sol-gel process. All of the aforementioned methods of layer application, except plasma spraying, can be used for both the one-stage sintering process and the two-stage sintering process as described above. The plasma-sprayed layers do not need to be sintered again and may already have their desired properties once the layer is applied. However, a subsequent temperature treatment may be advantageous.
[0057] Each of the above-mentioned methods of layer application can be combined with the already mentioned options for different material compositions or material properties and processing parameters during sintering. Furthermore, one or more layers of ceramic insulator 5 can be realized by all of the mentioned methods.
[0058] A grain size gradient can be set through the ceramic insulator 5 by selecting different material compositions or properties in each layer of the ceramic insulator 5 or by sintering each of these layers individually. Furthermore, interactions, particularly diffusion, at layer boundaries of layers having different material compositions or properties result in grain size gradients at these layer boundaries. Such grain size gradients prevent expansion or tensile cracking.
[0059] Already polarized actuators according to the invention were subjected to static life tests at constant voltage (DC). At the same time, prior art actuators with ceramic insulators were investigated. The control voltage was selected such that the actuators showed an active area expansion of 1.47‰. The mean useful life MTTF of the actuators was determined for each test group based on the time to failure of the actuators. The determined values and test conditions can be seen from Table 1.
[0060] The MTTF was calculated for the polymer coated actuators using the respective manufacturer's useful life formula.
[0061] The MTTF of an actuator according to the invention at 25° C. and 30% relative humidity was determined by extrapolation based on a series of tests.
[0062] [Table 1] [Explanation of symbols]
[0063] 1 Stacking 2 electrodes 3 External electrode 4 Connection Leads 5. Ceramic insulators
Claims
1. An electromechanical actuator comprising a stack arrangement (1) made of a ceramic base material having electromechanical properties and electrodes (2) and a ceramic insulator (5) for use of said actuator in a wet environment, the structures of said ceramic insulator (5) having a smaller average grain size than the structures of said ceramic base material, the insulator (5) has a material composition different from the ceramic base material; An actuator, characterized in that the material of the insulator (5) is doped with a grain growth inhibitor.
2. 2. The actuator according to claim 1, characterized in that the ratio of the average grain size of the insulator (5) to the ceramic base material is ≦3 / 4, preferably ≦1 / 2, particularly preferably ≦1 / 3.
3. 3. The actuator according to claim 1, wherein the average grain size of the insulator is less than or equal to 20 μm, preferably less than or equal to 5 μm, particularly preferably less than or equal to 1 μm.
4. An actuator according to any one of claims 1 to 3, characterized in that the average grain size of the ceramic base material decreases towards the insulator (5).
5. Actuator according to any one of claims 1 to 4, characterized in that the insulator (5) is made of electromechanical material, preferably of piezoelectric material, particularly preferably of piezoelectric ceramic material.
6. An actuator according to any one of the preceding claims, characterized in that the insulator (5) is impermeable to water vapour / moisture.
7. 7. The actuator according to claim 1, characterized in that the insulator (5) is made of at least one layer, preferably two or three layers, the total thickness of the insulator (5) being equal to or less than 500 μm, preferably equal to or less than 100 μm, particularly preferably equal to or less than 60 μm.
8. An actuator according to any one of claims 1 to 7, characterized in that two external electrodes (3) are provided for contacting the electrodes (2) in the stack arrangement (1), arranged on the same outer surface or on two different outer surfaces of the actuator, at least one electrode-free outer surface of the actuator being provided with the ceramic insulator (5).
9. 9. The actuator according to claim 1, wherein the ceramic base material and the electrodes (2) are arranged along a stack axis, the stack arrangement (1) has two end faces aligned perpendicular to the stack axis and at least one side face extending between the end faces, and the ceramic insulator (5) on the at least one side face extends from one end face to the other end face.
10. A method for manufacturing an electromechanical actuator according to any one of claims 1 to 9, comprising the steps of: A: forming a stack arrangement (1) from electrodes (2) and from a ceramic base material having electromechanical properties; B: providing a ceramic insulator (5) in said stack arrangement (1) such that the structures of the insulator (5) have an average grain size smaller than the structures of the ceramic base material.
11. Partial steps below: A1: Partial step of forming said stack arrangement (1) from said electrodes (2) and from green tapes made of said ceramic base material; A2: A partial step of sintering the stack arrangement (1) so that the ceramic base material is converted into a solid ceramic structure. The method of claim 10, comprising at least one of:
12. Partial steps below: B1: Partial step of applying at least one, some or all layers of said insulator (5) onto said stack arrangement (1) by coating, injection moulding, plasma spraying, preferably with a green tape, dip coating, spraying, preferably in a ceramic slurry, and / or by a sol-gel process, B2: A partial step of sintering the ceramic insulator (5) and optionally the ceramic base material, so that the ceramic insulator (5) and optionally the ceramic base material are converted into a solid ceramic structure; B3: A sub-step of setting the average grain size of the insulator (5) and possibly of the ceramic base material by selecting different materials for the ceramic base material and the ceramic insulator (5) and / or by selecting the process parameters during sintering. The method according to claim 10 or 11, comprising at least one of the following:
13. C: A method according to any one of claims 10 to 12, comprising the step of poling the ceramic base material, and preferably the ceramic insulator (5), to set the electromechanical properties of the actuator.
14. 14. The method according to any one of claims 10 to 13, wherein in step A the stack arrangement is formed from electrodes (2) and a ceramic base material along a stack axis, the stack arrangement (1) having two end faces oriented perpendicular to the stack axis and at least one side face extending between the end faces, and in step B the stack arrangement (1) is provided with the ceramic insulator (5), the ceramic insulator (5) extending from one end face to the other end face on the at least one side face.
Citation Information
Patent Citations
Production of piezoelectric material for actuator
JP1995069722A
Stacked piezo-electric element and fuel injection equipment
JP2005203706A
Laminated piezoelectric element
JP2007266468A
laminate
JP2014072511A
Laminated type piezoelectric element, and piezoelectric actuator and mass flow controller using the same
JP2015142027A
